Knowledge gaps on drivers of change in East African dry forests: insights from a systematic literature review - Maria Alejandra Aguilar-Tomasini; Jennifer Joy West; Aster Gebrekirstos; Tron Eid; Abrha Megos Meressa; Meley Mekonen Rannestad (Ecological Processes)
Abstract Dry forests, on which millions of the world’s impoverished individuals rely, are among the most threatened ecosystems on Earth. Understanding the drivers of change affecting the dynamics of dry forests, the ecosystem services (ES) they provide, and the people who depend on them is fundamental for developing sustainable forest management plans. This review aims to identify the main drivers of change in East African dry forests using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After applying inclusion and exclusion criteria to the data, a total of 330 papers were analyzed, and the information obtained was systematically classified and categorized. The findings from the review highlight three important knowledge gaps: (1) limited research in specific geographic areas, (2) inadequate interdisciplinary collaboration in comprehansively studying drivers of change, and (3) insufficient exploration of indirect drivers and their mechanisms. Recommendations for future research include strengthening interdisciplinary approaches, exploring indirect drivers, and addressing country-specific drivers in diverse contexts. These insights aim to facilitate the development of improved management and policy measures for the sustainable use and conservation of East African dry forests.